FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEBIASAAN DAN KUALITAS SARAPAN SISWA KELAS V DI SDN SENDANGMULYO 04 KECAMATAN TEMBALANG, SEMARANG TAHUN 2015 - Sylga Cahya Gemily; Ronny Aruben; Suyatno Suyatno (Jurnal Kesehatan Masyarakat (Undip), 2017)
Breakfast can provide around 15-30% of daily nutritional requirements, maintain physical endurance and increase work productivity. In Indonesia, 40% of children skipped breakfast and obtain energy intake less than 15% of daily nutritional requirements. The purpose of this study was to analyze the factors that related the habits and quality of breakfast at fifth grade students at  state primary schools Sendangmulyo 04 District Tembalang, Semarang. This study used descriptive research with cross sectional approach. The method used is quantitative and qualitative where quantitative to find out the habits and the quality of breakfast and related factors and qualitative to find out the reasons behind it. The population in this study was a fifth grade students in State Elementary School 04 Sendangmulyo District Tembalang, Semarang with 63 samples taken by using purposive sampling method. Data analysis of quantitative methods was univariate and bivariate with 95% of level significance and qualitative method used inductive analysis. The results showed that there was a significant relationship between the sexes (p=0,002), maternal education (p=0,023), maternal occupation (p=0,023), breakfast habits in family (p=0,028) and family encouragement (p=0,000) with breakfast habits. There was a significant relationship between breakfast habits in families with breakfast quality  (p=0,027). The conclusion was that most (67%) in the fifth grade students of State Elementary School District Tembalang 04 Sendangmulyo had breakfast habits and most (61,9%) had poor quality of breakfast. Factors related to the habits and the quality of the breakfast was breakfast habits in families .